Cardiovascular disease trends in Nepal – An analysis of global burden of disease data 2017. (October 2020) - Bhattarai, Sanju; Aryal, Anu; Pyakurel, Manita; Bajracharya, Swornim; Baral, Phanindra; Citrin, David; Cox, Helen; Dhimal, Meghnath; Fitzpatrick, Annette; Jha, Anjani Kumar; Jha, Niharika; Karmacharya, Biraj Man; et al.
Abstract: Cardiovascular diseases (CVDs) are the leading cause of disease burden globally, disproportionately affecting low and middle-income countries. The continued scarcity of literature on CVDs burden in Nepal has thwarted efforts to develop population-specific prevention and management strategies. This article reports the burden of CVDs in Nepal including, prevalence, incidence, and disability basis as well as trends over the past two decades by age and gender. We used the Institute of Health Metrics and Evaluation's Global Burden of Diseases database on cardiovascular disease from Nepal to describe the most recent data available (2017) and trends by age, gender and year from 1990 to 2017. Data are presented as percentages or as rates per 100, 000 population. In 2017, CVDs contributed to 26·9% of total deaths and 12·8% of total DALYs in Nepal. Ischemic heart disease was the predominant CVDs, contributing 16·4% to total deaths and 7·5% to total DALYs. Cardiovascular disease incidence and mortality rates have increased from 1990 to 2017, with the burden greater among males and among older age groups. The leading risk factors for CVDs were determined to be high systolic blood pressure, high low density lipoprotein cholesterol, smoking, air pollution, a diet low in whole grains, and a diet low in fruit. CVDs are a major public health problem in Nepal contributing to the high DALYs with unacceptable numbers of premature deaths. There is an urgent need to address the increasing burden of CVDs and their associated risk factors, particularly high blood pressure, body mass index and unhealthy diet.